2012
DOI: 10.1124/mol.112.080184
|View full text |Cite
|
Sign up to set email alerts
|

Fe2+ Block and Permeation of CaV3.1 (α1G) T-Type Calcium Channels: Candidate Mechanism for Non–Transferrin-Mediated Fe2+ Influx

Abstract: Iron is a biologically essential metal, but excess iron can cause damage to the cardiovascular and nervous systems. We examined the effects of extracellular Fe 2ϩ on permeation and gating of Ca V 3.1 channels stably transfected in HEK293 cells, by using whole-cell recording. Precautions were taken to maintain iron in the Fe 2ϩ state (e.g., use of extracellular ascorbate). With the use of instantaneous I-V currents (measured after strong depolarization) to isolate the effects on permeation, extracellular Fe 2ϩ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 58 publications
3
20
1
Order By: Relevance
“…However, the mechanism of extracellular Fe 2+ entry into the cardiomyocytes through TTCC in iron overload conditions may be similar to LTCC. As expected, a previous study found that Ca V 3.1 TTCC was a significant portal for Fe 2+ entry into cells leading to an iron overload condition49. Consistent with a recent study indicated that at a high concentration of free Fe 2+ may compete with a Ca 2+ influx into the myocardium through Ca 2+ channels by both LTCC and TTCC50.…”
Section: Discussionsupporting
confidence: 88%
“…However, the mechanism of extracellular Fe 2+ entry into the cardiomyocytes through TTCC in iron overload conditions may be similar to LTCC. As expected, a previous study found that Ca V 3.1 TTCC was a significant portal for Fe 2+ entry into cells leading to an iron overload condition49. Consistent with a recent study indicated that at a high concentration of free Fe 2+ may compete with a Ca 2+ influx into the myocardium through Ca 2+ channels by both LTCC and TTCC50.…”
Section: Discussionsupporting
confidence: 88%
“…This is supported by our previous reports, which demonstrated that TTCC re-expression in the heart of thalassaemic mice could be detected by real-time PCR and microarray (Kumfu et al , 2012a. Moreover, Lopin et al (2012) demonstrated that Fe 2+ inhibited Ca 2+ currents and that Fe 2+ could enter cardiomyocytes through the TTCC in iron-overloaded conditions. These findings suggest that the TTCC could play an important role in cardiac iron uptake in iron-overloaded conditions.…”
Section: Discussionsupporting
confidence: 86%
“…It has been shown that L-type calcium channels (LTCCs), T-type calcium channels (TTCCs) and divalent metal transporter1 (DMT1) play a role in iron uptake into the heart in a iron-overloaded conditions (Tsushima et al 1999;Crowe & Bartfay, 2002;Oudit et al 2003;Kumfu et al 2011Kumfu et al , 2012aLopin et al 2012;Musumeci et al 2013). Once iron is taken up into the cells, it is either stored as ferritin or transferred across the cell membrane into the blood circulation by the iron exporter ferroportin (Gunshin et al 1997;Fleming et al 1998;Abboud & Haile, 2000;Donovan et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chattipakorn, 2012; Kumfu et al, 2011;Lopin, Gray, Obejero-Paz, Thevenod, & Jones, 2012) and L-type calcium channels (LTCC) (Crowe & Bartfay, 2002;Fernandes et al, 2013;Oudit et al, 2003). Studies regarding Lcn2-mediated iron accumulation in iron-overloaded cardiomyocytes that are concurrently treated with iron-chelating therapeutic agents and antagonists of the aforementioned ironimporting systems are also lacking.…”
mentioning
confidence: 99%